PENGARUH MEDIA PEMBELAJARAN ROBOOK ( RODA BERPUTAR DAN POP UP BOOK ) TERHADAP HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN IPS DI SDN DUKUH KUPANG II SEMESTER GANJIL TAHUN AJARAN 2024/2025 - Fitrianto, Fedri; Prastyo, Danang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by students who were less enthusiastic and enthusiastic about following lessons because teachers had not yet mastered, innovated, been creative and utilized technological developments. This research aims to determine the significant influence of using Robook media on the learning outcomes of class V students at SDN Dukuh Kupang II Surabaya. This type of research is quantitative research. With a Quasi Experimental research design with Post Test Only Control form. The sample for this research was students in class V-A and students in class V-B. The data collection technique uses a post test sheet. The data analysis techniques used are the normality test, homogeneity test, and hypothesis testing in the form of a t-test using the SPSS 25 application. Based on the results of calculations using the SPSS application, it shows that the research results obtained by the test results are less than the predetermined significance value. This means that this explains that Ho was rejected, thus explaining that there is an influence of ROBOOK media (Wheel Spin and Pop Up Book) on the learning outcomes of students at SDN Dukuh Kupang II Surabaya